Proceedings of the 2nd Workshop on Language, Literature and Society for Education 2019
DOI: 10.4108/eai.21-12-2018.2282576
|View full text |Cite
|
Sign up to set email alerts
|

The Coastal Culture of the People of Indonesia and Malaysia the Folklore Malin Kundang and Si Tanggang

Abstract: Folk stories are one of the literary works that describe the condition of the local community and contain cultural values. Indonesian folklore Malin Kundang has a connection between coastal culture and Si Tanggang folklore from Malaysia. The purpose of this study was to determine the relationship of coastal culture to the folklore of Malin Kundang with Si Tanggang folklore. The research method uses descriptive research. Qualitative research forms. The data source is in the form of document review. Document stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 4 publications
0
3
0
Order By: Relevance
“…This research has the same object related to nature as other researchers who uncover the concept of the role of nature from the view of Malays based on its type in the Ediruslan Pe Amanriza's Dikalahkan Sang Sapurba novel [4]. Another research found contains the relationship of coastal culture between Malin Kundang and Si Tanggang folklores [5]. The other research found the form and implementation of sustainable tourism based on ecological wisdom [6].…”
Section: Introductionmentioning
confidence: 70%
“…This research has the same object related to nature as other researchers who uncover the concept of the role of nature from the view of Malays based on its type in the Ediruslan Pe Amanriza's Dikalahkan Sang Sapurba novel [4]. Another research found contains the relationship of coastal culture between Malin Kundang and Si Tanggang folklores [5]. The other research found the form and implementation of sustainable tourism based on ecological wisdom [6].…”
Section: Introductionmentioning
confidence: 70%
“…This second story is taken from library data. Si Tanggang's story was examined by Suwartini (2018); Radzi (2015); and Ismail (2015). The two folk stories discussed in this article are titled "Batu Ajuang Batu Peti" from West Sumatra.…”
Section: Methodsmentioning
confidence: 99%
“…Based on the previous studies related to ethnographic exploration and cultural expression related to [2] the relation of coastal cultures with Malin Kundang and Si Tanggang folktale; [3] the traditions of Dawuhan Village in Banyumas as the cultural heritage; [4] the cultural representation found in Dewi Rengganis folktale from Lelakaq Sasak, Lombok; [5] the exploration of cultural elements in Mexico, USA by utilizing folktales to overcome the cultural competition; [6] the cultural heritage of Prigi shore related to Sajen Slametan Njangkar as the symbol of particular message to the Queen of Southern Sea, Kanjeng Ratu Nyi Roro Kidul; [7] the luck, risk, and socio-political implication of the ritual observation to the coastal fishing village; [8] the depiction of the fishermen's local wisdom based on the language tradition and livelihood at the Southern Sea in Kebumen Regency through the ethnolinguistic study; [9] the traditional folktales adopted as the Kazakh cinematography and analyzed specifically through the ethnic values, culture, tradition, and spiritual development; [10] the myth or belief to the Sea Gods based on the Kuroshio Oceanic culture related to maritime tradition and social interaction in Jeju Island, Zhoushan Island, and Ryukyu Island; [11] the meaning and cultural values of Tapis Inuh coastal society in South Lampung.…”
Section: Introductionmentioning
confidence: 99%